Voice and accountability: the role of maternal, neonatal and child health committee - Leppard, Margaret; Rashid, Sarawat; Rahman, Atiya; Akter, Mahmuda; Hashima-E-Nasreen (BRAC Research and Evaluation Division (RED), 2019)
The study aims to explore how the MNCH committee encouraged community participation and how its communication activities empowered the community people to ensure the healthcare needs of the poor and disadvantaged people. A range of qualitative method was used in the study. In-depth interview, focus-group discussion, informal discussion, observation and document review were used as data collection method. This study conducted in two sub-districts of Nilphamarl and Mymensingh districts of Bangladesh during February-April 2010. Thematic content analysis technique was followed. Findings reveal that the committee members took necessary steps to solve the maternal complication by referral, follow-up of referred cases, and providing financial support to the extreme poor if needed, and the committee helped increase the availability of healthcare service providers and Improve the nature of services accessible to the community people. However, the capacity of the committees to raise the voice of poor people was fairly limited due to lack of adequate orientation of the committee members and also for lack of publicity about their roles. Besides, the committee could not run properly due to disagreement between power and literacy among the committee members. The MNCH committee has potential as it allowed the people's voice and could, thus, serve as a pathway through which ordinary people could hold local health authorities and local service providers to account. The findings informed the further development of an enabling environment in which the voices of MNCH committee members and community people would be stronger.